The diversity and habitat association of medium and large mammals in the Dhidhessa Wildlife Sanctuary, Southwestern Ethiopia - Girma Gizachew Tefera; Tadesse Habtamu Tessema; Tibebu Alemu Bekere; Tariku Mekonnen Gutema (PLoS ONE, 2025)
Understanding species diversity and habitat association is the baseline for developing conservation plan. The study aimed to assess diversity, abundance and habitat association of medium and large sized mammals in the Dhidhessa Wildlife Sanctuary (DWS), Southwestern Ethiopia. The survey was conducted from December 2022 to July 2023, both in the wet and dry seasons. A stratified random sampling design was applied to stratify the study area in to four (wooded grassland, riparian forest, seasonally flooded grassland, and savanna grassland) strata based on vegetation and habitat type. Lines transect survey, sensor camera trapping, and indirect and direct evidence methods were used to collect data during wet and dry seasons. Data were analyzed using the chi square test and species diversity indexes. Twenty -seven mammalian species were recorded for the area. Order Artiodactyla which had the highest number of species (eleven = 11) followed by the, order Carnivora (n = 9). While, orders Rodentia and Tubulidentata each represented by one species. Papio anubis (n =  500, 24.9%) were the most abundant species followed by Hippopotamus amphibious (n =  364, 17.8%) in the present study area in both wet and dry seasons. But Panthera pardus (n = 13, 0.64%) and Civettictis civetta (n = 13, 0.64%) were the least abundant species in the present study area. Riparian forest had the highest number of species (n = 732, 36.3%) followed by savanna grassland (n = 615, 30.5%). Savanna grassland held the highest species diversity of medium- and large-sized mammals (H′ =  2.44). Seasonally flooded grasslands (E =  0.6849) and riparian forests (E =  0.4889) showed the highest and lowest evenness of the mammalian species, respectively. Therefore, DWS’s primary priority should be creating management plans to reestablish the sanctuary as a fully functional sustainable ecosystem and ensuring the social and economic viability of the surrounding community.